2017
DOI: 10.17706/ijbbb.2017.7.3.162-168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Black Cumin Seed Oil Role (BCSO) on a Decline in eNOS Expression and Plasma NO Levels: Initial Studies Kemopreventive BCSO for Lung Cancer

Abstract: BCSO is effective as an anti-aging agent in cultures of endothelial and macrophage exposed 7.12, dimethyl-benzantracene (DMBA). Reactive radicals damage endothelial tissue, cause inflammatory reactions and have a role in carcinogenesis. Excessive eNOS expression linked to chronic inflammation and carcinogenesis of lung cancer. The research objective was to determine the effect of BCSO on the expression of eNOS and NO levels of macrophage SD rats exposed DMBA.A study used 36 rats SD that divided into 6 groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The BCSO group of 6.8 mg/kg BW/day was able to improve the immune response to the same level as the BCSO group of 68 and 136 mg/kg BW/day and may be safer with smaller doses. The results of this study are consistent with previous studies showing that BCSO is both antioxidative and immunomodulatory [16][17][20][21][22]. Data from this study support the results of previous studies, namely the effect of BCSO on the number of CD4CD25Treg.…”
Section: Number Of Cd4 Th and Cd4cd25 Tregsupporting
confidence: 92%
See 1 more Smart Citation
“…The BCSO group of 6.8 mg/kg BW/day was able to improve the immune response to the same level as the BCSO group of 68 and 136 mg/kg BW/day and may be safer with smaller doses. The results of this study are consistent with previous studies showing that BCSO is both antioxidative and immunomodulatory [16][17][20][21][22]. Data from this study support the results of previous studies, namely the effect of BCSO on the number of CD4CD25Treg.…”
Section: Number Of Cd4 Th and Cd4cd25 Tregsupporting
confidence: 92%
“…As CD4 Th increases, the production of IL-2, IL-12 and IFN-y cytokines also increases, thus increasing the number and activity of CD8 cytolytic lymphocytes [8]. It has been demonstrated that BCSO decreases eNOS activity, lymphocyte proliferative activity and differentiation increases the production of IL-12 cytokines by macrophages and inhibits inflammation through inhibition of prostaglandin production [15,[21][22]24].…”
Section: Number Of Cd4 Th and Cd4cd25 Tregmentioning
confidence: 99%
“…2, April 2022: 1565-1570 1566 homeostasis of blood vessels. Disruption of endothelial homeostasis causes the impaired function of nitric oxide synthase (NOS) so that the production of nitric oxide (NO) compounds, which play an essential role in regulating blood flow, is reduced [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some medicinal plants can be used to prevent cardiovascular and degenerative diseases, cancer, diabetes mellitus, and aging/senility [11], [12]. These plants have shown antioxidative [13], immunomodulatory [14], antihypertensive [15], antibacterial, hypoglycemic [16], anti-dyslipidemic, cytotoxic, and antiproliferative activities [17]. Transforming the plants into medicinal preparations in herbs and standardized herbal medicines will increase their use-value and economic value.…”
Section: Introductionmentioning
confidence: 99%